2015
DOI: 10.3390/s150819264
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Systematic Errors of Electronic Distance Meters for Measurement of Short Distances

Abstract: In modern industrial geodesy, high demands are placed on the final accuracy, with expectations currently falling below 1 mm. The measurement methodology and surveying instruments used have to be adjusted to meet these stringent requirements, especially the total stations as the most often used instruments. A standard deviation of the measured distance is the accuracy parameter, commonly between 1 and 2 mm. This parameter is often discussed in conjunction with the determination of the real accuracy of measureme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 15 publications
(13 reference statements)
1
10
0
Order By: Relevance
“…ToA and ToF are used in systems based on interferometry [ 2 ], time of flight cameras [ 3 , 4 ] or ultrasound [ 5 ], in which the sender and receiver share hardware and can detect when the signal is emitted and received, and therefore, measure signal flight time or the phase difference of arrival (PoA-PDoA). The sender and the receiver are distant, so they must be synchronized in order to obtain the propagation times.…”
Section: Introductionmentioning
confidence: 99%
“…ToA and ToF are used in systems based on interferometry [ 2 ], time of flight cameras [ 3 , 4 ] or ultrasound [ 5 ], in which the sender and receiver share hardware and can detect when the signal is emitted and received, and therefore, measure signal flight time or the phase difference of arrival (PoA-PDoA). The sender and the receiver are distant, so they must be synchronized in order to obtain the propagation times.…”
Section: Introductionmentioning
confidence: 99%
“…Estimating the positioning errors of total stations is even more complicated due to the combination of EDM and angle sensors (Walker and Awange, 2018). Braun et al (2015) thoroughly investigated the accuracy and precision of industrystandard EDM devices over a well-calibrated distance of 40 m. They found that the accuracy varied from 0-4 mm, with some devices showing dependence on the measurement Figure 3. Illustration of the influence that the instrument resolution has on the measurement error: a continuous, time-variable head is measured at discrete time intervals by instruments with analogue-to-digital conversion resolution of 5, 2 and 0.1 mm.…”
Section: Relative Positioning Using Traditional Surveyingmentioning
confidence: 99%
“…distance. We use the precision of 0.5 mm stated by Braun et al (2015) for our error analysis (Table 1).…”
Section: Relative Positioning Using Traditional Surveyingmentioning
confidence: 99%
See 1 more Smart Citation
“…Open GMI may suffer from a time delay in the water level response to changes in subsurface pore pressure, either because the well screen is partially clogged or improperly sized or because the well volume is so large that water cannot flow fast enough through the surrounding porous media and well screen to allow equilibration of the water level inside the well with the groundwater pressure (e.g., Hvorslev, 1951). In low-permeability materials like compacted peat or finegrained sediments, time lags can be on the order of hours or even longer, which precludes the registration of the response to rapid processes such as for example river flooding events (Hanschke and Baird, 2006) but also to water level changes induced by pumping, ocean tides or atmospheric pressure changes (e.g., Bredehoeft, 1967). Observation wells may also take appreciable time to readjust after the water level inside was raised by water displaced by inserting measurement instruments.…”
Section: Miscellaneous Errorsmentioning
confidence: 99%